Graphene oxide wrapped Cu3V2O7(OH)2 · 2H2O nanocomposite with enhanced electrochemical performance for lithium-ion storage. (19th February 2019) - Li, Malin; Wei, Zhixuan; Wang, Dongxue; Zhang, Zhongyu; Wang, Chunzhong; Chen, Gang; Du, Fei
Abstract: Transition metal oxides (TMOs) are widely accepted as one of the alternatives for the graphite anode in lithium-ion batteries (LIBs) owing to the high specific capacity and facile synthesis of nanoscale materials facilitating fast ionic transfer. However, the lower electronic conductivity always impedes the application of TMOs. Herein, we report a graphene oxide wrapped layer-structured Cu3 V2 O7 (OH)2 · 2H2 O nanocomposite (CVO/GO) synthesized via an in situ co-precipitation method. It is corroborated that the introduction of GO not only provides more active sites for lithium-ion storage, but also improves the charge transfer rate of the electrode, issuing an enhanced electrochemical performance. As expected, the CVO/GO nanocomposite exhibits an ultrahigh specific capacity of 870 mA h g −1 at 0.1 A g −1 compared with CVO nanoparticles. Even at a high current density of 5 A g −1, a specific capacity of 158 mA h g −1 could be achieved for the CVO/GO nanocomposite.